2010
DOI: 10.1186/1471-2407-10-557
|View full text |Cite
|
Sign up to set email alerts
|

Triple negativity and young age as prognostic factors in lymph node-negative invasive ductal carcinoma of 1 cm or less

Abstract: BackgroundWhether a systemic adjuvant treatment is needed is an area of controversy in patients with node-negative early breast cancer with tumor size of ≤1 cm, including T1mic.MethodsWe performed a retrospective analysis of clinical and pathology data of all consecutive patients with node-negative T1mic, T1a, and T1b invasive ductal carcinoma who received surgery between Jan 2000 and Dec 2006. The recurrence free survival (RFS) and risk factors for recurrence were identified.ResultsOut of 3889 patients diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
44
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 32 publications
9
44
0
2
Order By: Relevance
“…These results are in line with those already presented in two previous studies [8,21] In a Korean analysis, patients with Triple Negative disease had a significantly lower Relapse-Free…”
supporting
confidence: 92%
See 1 more Smart Citation
“…These results are in line with those already presented in two previous studies [8,21] In a Korean analysis, patients with Triple Negative disease had a significantly lower Relapse-Free…”
supporting
confidence: 92%
“…After a median follow-up of 60 months, authors showed that age younger than 35 years was significantly associated with a higher rate of recurrence HR 4.91; 95%CI=1.01-23.76; P=0.048) [21]. In our previous published study we explored patterns of Current study adds important information about the prognosis of very young women with breast cancer; also when tumour size is less than 1 centimetre age less than 35 is a significant risk factor for a reduced BCS and overall survival compared to older patients.…”
mentioning
confidence: 99%
“…Multiple studies have indicated a strong prognostic relation between patients with TNBC and increased LRR, and this also applied to early stage breast cancer. [10][11][12][13]18 In patients with ETNBC, Abdulkarim et al 14 recently reported that the LRR risk in the modified radical mastectomy without PMRT group was 2.5 times higher than in the breast-conserving therapy group among those with T1-T2N0 disease (4% vs 10%; P 5 .027). This has sparked an intense debate about re-evaluating the role of PMRT for ETNBC, a subgroup for which it was previously assumed that PMRT was not clearly indicated.…”
Section: Discussionmentioning
confidence: 99%
“…More studies since have demonstrated that patients who have TNBC are at a higher risk of LRR, 10,11 including those who have very early disease. 12,13 Moreover, in a recent article by Abdulkarim et al 14 reporting exclusively on TNBC, the highest LRR rates were observed in patients who underwent modified radical mastectomy without PMRT compared with those who underwent modified radical mastectomy and received PMRT or breast-conserving therapy. This highlights the need to re-evaluate prognostic factors in early stage TNBC (ETNBC) and the utility of PMRT.…”
Section: Introductionmentioning
confidence: 99%
“…Survival rate compared to hormone receptor-positive and/or HER2-positive patients (p=0.016); in the multivariate analysis, triple negativity was an independent prognostic factors of recurrence (HR 4.96; 95% CI: 1.00-23.1; p=0.018) [21].…”
mentioning
confidence: 99%